Prediction of Turbofan Engine Noise Considering Diffraction at the Duct Outlet - SNAKOWSKA, Anna; IDCZAK, Henryk (Archives of Acoustics, 2008)
The sound field produced by jet engine is extremely complicated due to nonlinear and turbulent effects and thus cannot be predicted exactly. The rise in air-transport causes a strong demand to evaluate the field with better accuracy than that given by baffled outlet and Kirchhoff integral. In the paper the radiation of sound from the inlet is considered with respect to results obtained for semi-infinite rigid cylindrical duct. Introduction of such a model, assuming the duct to be empty inside, is justified by increase of the by-pass ratio and the energy distribution inside the duct. The subsonic mean flow is assumed and the adequate wave equation is considered. The Prandtl–Glauert transformation is adopted.